2017
DOI: 10.3390/f8060207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Climate Change on the Development of Tree Plantations for Biodiesel Production in China

Abstract: Biodiesel produced from woody oil plants is a promising form of renewable energy but a combination of tree plantations' long cultivation time and rapid climate change may put large-scale production at risk. If plantations are located in future-unsuitable places, plantations may fail or yield may be poor, then significant financial, labor, and land resources invested in planting programs will be wasted. Incorporating climate change information into the planning and management of forest-based biodiesel productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Among SDMs, the maximum entropy (MaxEnt) model is the most popular one to simulate species distribution based on species presence-only records, which are usually readily available from digital specimen museums and published literature [14][15][16]. The MaxEnt model has been widely used to evaluate the relationship between species distribution and determinant variables and to predict the response of species geographical distribution to global climate change [17][18][19][20]. Many studies have found that the MaxEnt model typically outperforms other methods in terms of high predictive accuracy and high tolerance to extremely small sample size [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Among SDMs, the maximum entropy (MaxEnt) model is the most popular one to simulate species distribution based on species presence-only records, which are usually readily available from digital specimen museums and published literature [14][15][16]. The MaxEnt model has been widely used to evaluate the relationship between species distribution and determinant variables and to predict the response of species geographical distribution to global climate change [17][18][19][20]. Many studies have found that the MaxEnt model typically outperforms other methods in terms of high predictive accuracy and high tolerance to extremely small sample size [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Species distribution models (SDMs) can be used effectively to predict the distribution of species (Guisan & Zimmermann, 2000; Phillips, Anderson, & Schapire, 2006), and they have been widely used to identify the potential distribution of invasive species (Broennimann & Guisan, 2008; Dai et al, 2018; Jiménez‐Valverde et al, 2011; Lamsal, Kumar, Aryal, & Atreya, 2018; Panda, Behera, & Roy, 2018; Thuiller et al, 2005). However, differences in model algorithms can create uncertainties by influencing the outcome of SDMs (Buisson, Thuiller, Casajus, Lek, & Grenouillet, 2010; Dai et al, 2017; Wiens, Stralberg, Jongsomjit, Howell, & Snyder, 2009; Wright, Hijmans, Schwartz, & Shaffer, 2015). Ensemble model (Araújo & New, 2007; Marmion, Parviainen, Luoto, Heikkinen, & Thuiller, 2009), which integrates multiple individual models, can reduce bias in predictions of species distribution (Araújo & New, 2007), and have been shown to provide robust estimates of invasive species' distribution (Meller et al, 2014; Poulos, Chernoff, Fuller, & Butman, 2012; Srivastava, Griess, & Padalia, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Biodiversity is generally accepted to be decreasing at an unprecedented rate (1-4). Among the many reasons for this, climate change is often regarded as one of the most significant drivers as it influences the growth and reproduction of species, thereby determining the natural distribution of species (4)(5)(6)(7)(8). The Intergovernmental Panel on Climate Change (IPCC) estimated that the average global temperature, which has increased by 0.85°C during the 20 th century, will continue to increase by at least 0.3-1.7 °C and at most by 2.6-4.8°C by 2100 (9).…”
Section: Introductionmentioning
confidence: 99%